Outdoor activities: basics and benefits - VUKIĆ, Željko; OPREAN, Alexandru (2024)
In a society where traditional classroom settings oftendominate the learning landscape, outdoor education provides abreath of fresh air by taking students beyond four walls andimmersing them in the natural environment. This educationalapproach embraces the great outdoors as a dynamic andinteractive classroom, offering a wide array of benefits andlearning opportunities for students of all ages..Outdoor education goes beyond simply teaching subjects inan outdoor setting. It is a holistic approach that aims to fosterpersonal, social, and environmental growth through experientiallearning. By engaging in a variety of outdoor activities, studentsdevelop a deeper connection with nature, gain practical skills,enhance their problem-solving abilities, and build resilience inthe face of challenges.